5y-9=8y-4y

Simple and best practice solution for 5y-9=8y-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-9=8y-4y equation:


Simplifying
5y + -9 = 8y + -4y

Reorder the terms:
-9 + 5y = 8y + -4y

Combine like terms: 8y + -4y = 4y
-9 + 5y = 4y

Solving
-9 + 5y = 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
-9 + 5y + -4y = 4y + -4y

Combine like terms: 5y + -4y = 1y
-9 + 1y = 4y + -4y

Combine like terms: 4y + -4y = 0
-9 + 1y = 0

Add '9' to each side of the equation.
-9 + 9 + 1y = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 1y = 0 + 9
1y = 0 + 9

Combine like terms: 0 + 9 = 9
1y = 9

Divide each side by '1'.
y = 9

Simplifying
y = 9

See similar equations:

| 9.7+x=11.24 | | 9x-5=2x+3 | | 4(5)+-20=0 | | 3x-2k=24x-16 | | 5x(x+12)=-180 | | 12.25+x=13.11 | | -2/p=4/11 | | 6x-84=3x-9 | | 3x(x+12)=2x(2x+4) | | -5+7x=3+9x | | n/5-5=7 | | -21z-33=30 | | 6x-4+6-2x=12 | | 5.2(2a-1)=7 | | 2h-12=2 | | -7x-24=312 | | 2x+40x= | | 4x-15(6-x)=-8(5-3x) | | -20p-5=-765 | | 77=5y-13 | | 16=4s-4 | | 9x+4.86=3x+12 | | 10x^2-50x-60=0 | | 7x-13=4x-4 | | 7a=10 | | 4y+70=6 | | 4u-10=24 | | 4x-15(6-x)=8(5-3x) | | 3r-7s=K | | 6/x=24/(30-2x) | | 13y+3=-335 | | 2x-8+6-x=16 |

Equations solver categories